2019
DOI: 10.1111/jch.13588
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the combination of inter‐limb blood pressure differences in the elderly: The Northern Shanghai Study

Abstract: Whether the combination of inter‐arm and inter‐leg systolic blood pressure differences (BPDs) and ankle‐brachial index is of clinical significance remains unclear. In this study, we aimed to investigate the association of the combination of inter‐limb systolic BPDs with cardiovascular risk factors and hypertension‐mediated organ damage (HMOD). A total of 2621 elderly subjects from the Northern Shanghai Study were divided into Group A, B, and C consisting of participants with 0, 1, and ≥2 abnormal inter‐limb sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Presently, there is a device available (Figure ) that can do these measurements more accurately and simultaneously by a technician within 5 minutes . In their study, Yu et al found that patients with higher ILimbSBPd values had a greater burden of CV risk factors, such as atherosclerosis (carotid plaque), arterial stiffness, and LVH than patients with lower or normal ILimbSBPd values. Taken all together, this study demonstrates that the combination of ILimbSBPd may be a better marker of generalized atherosclerosis than each individual IASBPd, ILSBPd, or ABI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there is a device available (Figure ) that can do these measurements more accurately and simultaneously by a technician within 5 minutes . In their study, Yu et al found that patients with higher ILimbSBPd values had a greater burden of CV risk factors, such as atherosclerosis (carotid plaque), arterial stiffness, and LVH than patients with lower or normal ILimbSBPd values. Taken all together, this study demonstrates that the combination of ILimbSBPd may be a better marker of generalized atherosclerosis than each individual IASBPd, ILSBPd, or ABI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new noninvasive vascular tests incorporating the simultaneous measurement of IASBPd and the inter‐leg SBP difference (ILSBPd) have been developed and when added to the FRS could further increase its predictive value. In this issue of the journal, Yu et al report on the predictive value of measuring the simultaneous IASBPd and ILSBPd in combination with the measurement of the ankle‐brachial index (ABI), by using an automated device (Collin VP‐1000). This devise illustrated in Figure is automated, can measure simultaneously the SBP in all 4 extremities by an oscillometric method, also calculate the ABI in addition to other tests, such as the pulse wave velocity (PWV), the pulse rate (PR), and the arterial waveforms by a technician within 5‐10 min, and provide a written report .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1,744 subjects with Hcy data available derived from the Northern Shanghai Study were included for the present study. The Northern Shanghai Study is an ongoing prospective and registered study (ClinicalTrial.gov Identifier NCT02368938) and has been described in detail in our previous articles ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…8 At the same time, some other research of our team has also revealed a new metabolic indicator of cardiovascular disease and key clinical indicators of early cardiovascular organ damage. [9][10][11] Based on these findings, we plan to conduct the Northern Shanghai Study II with an intent to achieve the following three research objectives: (1) establish the first Chinese-based database of all early cardiovascular organ structural and functional damage phenotypes, and establish a digital follow-up mechanism to create a prospective population-based cohort; (2) build a biobank (including blood, urine, faeces) for early cardiovascular organ damage in the Chinese population; and (3) explore a digital medication-based intervention and management system for early cardiovascular organ damage. This paper is to describe the design and method plan for this study.…”
Section: Open Accessmentioning
confidence: 99%